2010
DOI: 10.3832/ifor0543-003
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing-supported vegetation parameters for regional climate models: a brief review

Abstract: © iForest-Biogeosciences and Forestry © SISEF http://www.sisef.it/iforest/ 98 iForest (2010) 3: 98-101 Citation: Latifi H, Galos B, 2010. Remote sensing-supported vegetation parameters for regional climate models: a brief review. iForest 3: 98-101 [online: 2010-07-15] URL: http://www.sisef.it/iforest/show.php? id=543 Collection: NFZ Summer School 2009-Birmensdorf (Switzerland) Long-term ecosystem research: understanding the present to shape the future Guest Editor: Marcus Schaub (WSL, Switzerland)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Compared with the Pathfinder AVHRR land (PAL) dataset, the GIMMS NDVI has further eliminated the effects of calibration, geometry, viewing angle and volcanic aerosols (Tucker et al 2004). One of the most significant datasets available for large-scale vegetation studies was recently demonstrated (Myneni et al 1997;Nemani et al 2003;Rikie et al 2007), not only because of its relative continuity in temporal and spatial terms but also due to its high correlations with some vegetation parameters such as net primary production (NPP), leaf area index (LAI) and the fraction of photosynthetically active radiation absorbed by the vegetation canopy (FPAR) (Goward et al 1985;Myneni and Williams 1994;Purevdorj et al 1998;Latifi and Galos 2010).…”
Section: Ndvi Datasetmentioning
confidence: 99%
“…Compared with the Pathfinder AVHRR land (PAL) dataset, the GIMMS NDVI has further eliminated the effects of calibration, geometry, viewing angle and volcanic aerosols (Tucker et al 2004). One of the most significant datasets available for large-scale vegetation studies was recently demonstrated (Myneni et al 1997;Nemani et al 2003;Rikie et al 2007), not only because of its relative continuity in temporal and spatial terms but also due to its high correlations with some vegetation parameters such as net primary production (NPP), leaf area index (LAI) and the fraction of photosynthetically active radiation absorbed by the vegetation canopy (FPAR) (Goward et al 1985;Myneni and Williams 1994;Purevdorj et al 1998;Latifi and Galos 2010).…”
Section: Ndvi Datasetmentioning
confidence: 99%
“…Thus, LAI is one of the key biophysical variables required by many process models describing the soil/plant/atmosphere system (Baret & Buis 2008, Latifi & Galos 2010. Because canopies and some of their characteristics can be directly observed from above, LAI is among the major variables of interest in remote sensing analyses (Lee et al 2004), and its importance has led to considerable efforts to map its distribution over a variety of spatial and temporal scales (Cohen et al 2003, Morisette et al 2006, Zhao & Popescu 2009, Latifi & Galos 2010, Tang et al 2012. The majority of studies used (semi-) empirical relationships between LAI and combinations of spectral bands, namely vegetation indexes (VI), for LAI mapping (Baret & Buis 2008, Vuolo et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…The use of high-resolution true color and false color (VNIR) RGB composite aerial photos (also stereoscopic solutions) and multispectral satellite images, has become much easier during the last few decades. A multitude of environmental research has confirmed the possibility of using this geodata supported by GIS analyses for remote and automated environment monitoring in the area of nature protection, forestry, meteorology, climatology and hydrology (Coops, White 2003, Corona et al 2008, Drzewiecki et al 2014, Latifi, Galos 2010, Wężyk et al 2013. The role played by image 6 MARTA SzOSTAK, PIOTR WężyK, PAWEł HAWRyłO, MARTA PUCHAłA classification based on multi-source, multi-resolution and multi-temporal remote sensed data is ever increasing in the environmental studies field.…”
Section: Introductionmentioning
confidence: 93%